2021
DOI: 10.3390/s21041388
|View full text |Cite
|
Sign up to set email alerts
|

Shape Sensing of a Complex Aeronautical Structure with Inverse Finite Element Method

Abstract: The inverse Finite Element Method (iFEM) is receiving more attention for shape sensing due to its independence from the material properties and the external load. However, a proper definition of the model geometry with its boundary conditions is required, together with the acquisition of the structure’s strain field with optimized sensor networks. The iFEM model definition is not trivial in the case of complex structures, in particular, if sensors are not applied on the whole structure allowing just a partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The underlying idea on derivations of Eqs. (40)(41)(42)(43) is that energies required to break all associated bonds crossing unit crack between particles within the same ply or two adjacent plies of a laminate are the same with related critical energy release rate. It is also important to note that the bonds are assumed to fail only in tension because of the predominant mechanism of the delamination/fiber/matrix failure modes of a laminate.…”
Section:  mentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying idea on derivations of Eqs. (40)(41)(42)(43) is that energies required to break all associated bonds crossing unit crack between particles within the same ply or two adjacent plies of a laminate are the same with related critical energy release rate. It is also important to note that the bonds are assumed to fail only in tension because of the predominant mechanism of the delamination/fiber/matrix failure modes of a laminate.…”
Section:  mentioning
confidence: 99%
“…The most attractive ones including iMIN3 [32], iQS4 [33], and iCS8 [34] inverse-shell elements employ C 0 -continuous interpolation functions in accordance with the firstorder shear deformation theory (FSDT). Particularly, the iQS4 element has recently gained a popularity for shape sensing applications on simple/complex geometries, e.g., ship and offshore structures [35][36][37][38][39] and stiffened aerospace panels [40][41], due to its merits for practical modelling of large-scale structures with low-cost sensor measurement and highly accurate displacement estimations [42][43]. Several studies have shown the superior applications of iFEM/iQS4 approach Coupling of peridynamics and inverse finite element method for shape sensing and crack propagation monitoring of plate structures for damage identification in monolithic/stiffened structures having isotropic/orthotropic material properties [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…The iFEM has been successfully applied to the monitoring of a container ship [ 19 , 20 ], wind turbines [ 21 , 22 ], and to complex aeronautical structures [ 23 ]. Colombo et al in [ 24 ] developed an iFEM-based damage detection methodology, and current research is expanding towards damage identification and quantification [ 25 , 26 , 27 , 28 ]; very recent developments are in the direction of a non-deterministic displacement reconstruction [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quadrilateral inverse shell elements have been developed and applied using standard [ 33 , 34 , 35 ] and isogeometric [ 36 ] formulations. Recently, the iFEM has been experimentally applied to the full displacement field reconstruction of an aeronautical stiffened panel in [ 37 ].…”
Section: Introductionmentioning
confidence: 99%